2011
DOI: 10.1007/s10694-011-0214-0
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire on Firefighters’ Protective Clothing in China

Abstract: The objective of this work was to investigate the subjective perception of firefighters to the current in-service FPC to provide valuable data in FPC research and to guide the design of FPC in the future. A survey was carried out on 1201 firefighters from 119 fire stations, 25 provinces. The survey was related to basic information, trouble experienced, subjective evaluation, heat illness and injury experienced. Results indicate that the current in service FPC might restrict mobility of firefighters, and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…According to Kincl and colleagues, the discomfort response rate of the lower body was high when wearing PPE 19) . Huang and coworkers found that over 60% of firefighters (N=1,177) chose 'difficulty of movement' as their main problem and the most restricted parts due to PPE were the thigh, knee, and arm 16) . Activities while firefighting requires a wide ROM and a lot of joint motion in the arms and legs and PPE resulted in more restricted mobility and intensified physical strain.…”
Section: Muscle Fatigue and Injury Related To Ppementioning
confidence: 99%
See 1 more Smart Citation
“…According to Kincl and colleagues, the discomfort response rate of the lower body was high when wearing PPE 19) . Huang and coworkers found that over 60% of firefighters (N=1,177) chose 'difficulty of movement' as their main problem and the most restricted parts due to PPE were the thigh, knee, and arm 16) . Activities while firefighting requires a wide ROM and a lot of joint motion in the arms and legs and PPE resulted in more restricted mobility and intensified physical strain.…”
Section: Muscle Fatigue and Injury Related To Ppementioning
confidence: 99%
“…Japanese firefighters ranked ease of movement higher than comfort, protection, and safety. Huang and colleagues carried out a survey on experiences of trouble and injury and subjective evaluation of PPE for Chinese firefighters 16) . Bos and colleagues compared the work demands, health complaints, and disabilities of firefighters to office workers 17) .…”
Section: Introductionmentioning
confidence: 99%
“…Expected burns based on radiation values under low radiative heat intensity was also investigated, and the radiant heat protective performance and heat accumulation performance of the fire protection clothing in single-, double-, and multilayer systems were analyzed. [10][11][12] Cao Juan et al used a skin simulator to improve the thermal protective performance tester and conducted three kinds of multilayer fabrics of fire protection clothing under the thermal radiation of 15.4 kw/m 2 to predict the second-degree burns time, the influence of the thermal protective performance of the fabric with different degrees of water absorption was also investigated. 13,14 Yang et al used a coupled system of sweating human body model and thermal model to simulate the thermal response of the human body under transient conditions and verified the performance of the coupled system, the results indicate that the prediction results and experimental results are consistent in trend and absolute value.…”
Section: Introductionmentioning
confidence: 99%
“…He used the TPP method, RPP method, and SET method to design a compression device and used the simulated human skin sensor to improve the thermal protective performance tester. Expected burns based on radiation values under low radiative heat intensity was also investigated, and the radiant heat protective performance and heat accumulation performance of the fire protection clothing in single‐, double‐, and multilayer systems were analyzed 10‐12 . Cao Juan et al used a skin simulator to improve the thermal protective performance tester and conducted three kinds of multilayer fabrics of fire protection clothing under the thermal radiation of 15.4 kw/m 2 to predict the second‐degree burns time, the influence of the thermal protective performance of the fabric with different degrees of water absorption was also investigated 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Firefighters' protective clothing (FPC) constitutes critically important equipment in firefighting. Typical FPC consists of two parts: an outer shell and an inner linear [ 1 , 2 ]. In general, the moisture content in FPC material significantly affects the wearer's thermal and moisture comfort.…”
Section: Introductionmentioning
confidence: 99%